A Comprehensive Insight into the Role of Exosomes in Viral Infection: Dual Faces Bearing Different Functions - Mabroka H. Saad; Raied Badierah; Elrashdy M. Redwan; Esmail M. El-Fakharany (MDPI AG, 2021)
Extracellular vesicles (EVs) subtype, exosome is an extracellular nano-vesicle that sheds from cells' surface and originates as intraluminal vesicles during endocytosis. Firstly, it was thought to be a way for the cell to get rid of unwanted materials as it loaded selectively with a variety of cellular molecules, including RNAs, proteins, and lipids. However, it has been found to play a crucial role in several biological processes such as immune modulation, cellular communication, and their role as vehicles to transport biologically active molecules. The latest discoveries have revealed that many viruses export their viral elements within cellular factors using exosomes. Hijacking the exosomal pathway by viruses influences downstream processes such as viral propagation and cellular immunity and modulates the cellular microenvironment. In this manuscript, we reviewed exosomes biogenesis and their role in the immune response to viral infection. In addition, we provided a summary of how some pathogenic viruses hijacked this normal physiological process. Viral components are harbored in exosomes and the role of these exosomes in viral infection is discussed. Understanding the nature of exosomes and their role in viral infections is fundamental for future development for them to be used as a vaccine or as a non-classical therapeutic strategy to control several viral infections.